Effect of Diabetes Supportive Group and Network (DINET) Programme on Quality of Life for Diabetes Patients - Fakhriatul Falah; Rista Apriana; Gusti Ayu Putri Ariani (Journal of Nursing Science Update (JNSU), 2023)
Gorontalo is ranked 7th in the number of people with diabetes from 35 provinces in Indonesia. One of the causes is the lack of self-care management which impacts the low quality of life of diabetes patients. Supportive group existence is needed as social support for diabetes patient, mainly in the community. This study's purpose is to analyze the effect of the DINET programme on the quality of life of diabetic people. The research method used a pre-experimental design through one group of pre and post-test analyses. The supportive group support provided activities involving diabetes patients, including health education, focus group discussion, physical exercise, and using chatbots and group chat as communication media for support group members. The sample used was 16 people through the purposive sampling method. The instrument for quality of life used is the Diabetes Instrument Quality of Life (DQOL) from the American Diabetes Control and Complications Trial (DCCT) Research Group. The study's results showed a significant difference in the quality of life of DM patients after the intervention with a p-value of 0.000 (α < 0.05). The support group can be used as social support for diabetes patients to keep their discipline in self-care management to prevent dangerous complications.